UZBEKISTAN PUBLIC EDUCATION AND SCIENCE IN THE YEARS OF THE GREAT PATRIOTIC WAR (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article analyzes the activities of public education and science in Uzbekistan during the Great Patriotic War, as well as the problems that arose in these areas caused by martial law.